Effectiveness of nudges for sustainable transportation: A systematic review - Melin, Marianna; Makkonen, Anna; Yrjölä, Siiri; Peltomaa, Juha; Sandman, Nils; Tuominen, Jarno; Vuori, Kaisa; Tainio, Marko; Salo, Paula (Elsevier, 2026)
Behavior changes in the transportation sector are crucial for mitigating climate change. However, previous studies have not specifically reviewed the literature on nudging from the perspective of enhancing sustainable transport. Therefore, the objective of this systematic review is to assess whether nudge interventions are effective in fostering a transition toward more sustainable transport behaviors. A systematic data search was conducted using the Web of Science, Academic Search Premier, SocINDEX, and PsycINFO. The inclusion of articles was restricted to peer-reviewed scientific articles published in English. The selected criteria were as follows: (i) nudge intervention targeting transport behavior with the aim of lowering transport emissions, (ii) sample measurements before and after the intervention where applicable or had a continuous behavioral measurement, and (iii) the change in behavior was measured. Seventeen articles comprising 23 studies met the inclusion criteria. Sample sizes varied between 8 and 54,889. Risk of bias was assessed using the Joanna Briggs Institute's (JBI) critical appraisal tool. Relevant data from the studies were gathered into a working table that served as the basis for synthesizing the results. The nudge interventions varied considerably, and behavior was measured using different subjective and objective methods. Behavioral changes were observed in most studies (14/23). Thus, this review provides tentative evidence that nudge interventions can decrease car use and increase the use of sustainable travel modes and driving behaviors. No systematic patterns were found regarding the effectiveness of certain types of nudges or use of multiple nudges. One critical conclusion for future directions was the need of methodological and theoretical unification to gain a better understanding of the viability of nudges to alter transportation behavior.